2007
DOI: 10.1002/cm.20221
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression and dynamics of TPM1α and TPM1κ in myofibrils of avian myotubes

Abstract: From the four known vertebrate tropomyosin genes (designated TPM1, TPM2, TPM3, and TPM4) over 20 isoforms can be generated. The predominant TPM1 isoform, TPM1alpha, is specifically expressed in both skeletal and cardiac muscles. A newly discovered alternatively spliced isoform, TPM1kappa, containing exon 2a instead of exon 2b contained in TPM1alpha, was found to be cardiac specific and developmentally regulated. In this work, we transfected quail skeletal muscle cells with green fluorescent proteins (GFP) coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 40 publications
5
61
1
Order By: Relevance
“…There was no change in the dynamics of these two TM isoforms during cardiac myofibrillogenesis in contrast to the case in skeletal muscle cells [Wang et al, 2007]. These results are discussed in terms of thin filament assembly as premyofibrils transform into mature myofibrils in both cardiac and skeletal muscle cells [Wang et al, 2007].…”
Section: Introductioncontrasting
confidence: 56%
“…There was no change in the dynamics of these two TM isoforms during cardiac myofibrillogenesis in contrast to the case in skeletal muscle cells [Wang et al, 2007]. These results are discussed in terms of thin filament assembly as premyofibrils transform into mature myofibrils in both cardiac and skeletal muscle cells [Wang et al, 2007].…”
Section: Introductioncontrasting
confidence: 56%
“…Because of the large number of protein pairs possible in a complicated network such as the Z-band, an approach like this requires a large number of experiments: if one varies both acceptor and donor locations, each pair represents up to four FRET experiments that must be done. Experiments aimed at discovering stepwise changes associated with myofibril development add yet another layer of complexity to an already large data array [Rhee et al, 1997;Sanger et al, 2004Sanger et al, , 2005Golson et al, 2004;Wang et al 2005a,b;Wang et al, 2007]. We have shown that careful statistical analysis, in our case, multiple linear regression, can be used to extract meaningful information from multifaceted data sets.…”
Section: Discussionmentioning
confidence: 84%
“…The z-bodies of premyofibrils are located at the leading edges of the myotubes whereas the Z-bands of the mature myofibrils are best studied in the central shafts of the same myotubes ( Fig. 1) [Wang et al 2005a[Wang et al , 2007[Wang et al , 2008. To look for changes in molecular organization associated with Zband maturation, mYFP-alpha-actinin was co-expressed with mCFP-alpha-actinin in cultured quail skeletal myotubes.…”
Section: Alpha-actinin and Alpha-actininmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, tropomyosins fused to non-coiled-coil fluorescent proteins can incorporate into sarcomeres suggesting that the mutant tropomyosin in these families might not be completely non-functional. 34 If, however, the extended mutant a-tropomyosin in the present patients is nonfunctional, it would make these patients comparable to the NM patient homozygous for an early nonsense mutation in the TPM3 gene described by Tan et al 17 The present patients would then have no functional slow a-tropomyosin in their slow, type 1, muscle fibres, explaining why the type 1 muscle fibres are severely hypotrophic. The only functional tropomyosin in the patients' type 1 fibres would be whatever b-tropomyosin is present.…”
Section: Discussionmentioning
confidence: 66%